Does currency wealth or substitiution effect matters? recent evidence from money demand in China - Niaz Ahmad, Mohd Naseem; Masron, Tajul Ariffin; A. M., Hafizi; Kamaluddin, F. (Universiti Putra Malaysia Press, 2020)
This study investigates the stability of money demand function for China, using an innovation ARDL framework for co-integration test for the time period 1986-2018. Specifically, this study used narrow money (M1) and broad money (M2) as a measurement of money. To consider currency wealth and substitution effects, the estimated money demand model includes the real effective exchange rate in addition to income and interest rate. By incorporating the CUSUM and CUSUMSQ tests for stability in conjunction with co-integration analysis, the results confirm that there exists a stable long-run relationship for narrow money demand function. Importantly, the finding also discovers that real effective exchange rate appears to have a significant substitution effect on narrow money demand, which its omission can lead to biased result and misspecifications in the money demand function. This further corroborates that narrow money, (M1) act as a better measurement, which may have systematic influence on the trend of monetary aggregates.